Attitude and motivation in spoken English among semester 4 students in a Malaysian Polytechnic - a correlational study - Rabiatul Adawiyah Rayah; Nurul Aiman Mohd Jafre; Nor Aini Husain; Wan Rosedayu Wan Mohamad Nawawi (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2018)
English language proficient has currently becoming a necessary requirement in various fields of study and professions. However, most students refuse to speak in English because they are too concerned in making mistakes, lack of motivation, and low self-confidence. In learning English, attitude and motivation are very closely related. A learner with positive attitude towards learning a language has a high tendency of motivation towards it. Therefore, the main objective of the research was to investigate the correlation between the items of attitude and motivation in spoken English among semester 4 students at Politeknik Sultan Mizan Zainal Abidin (PSMZA). The methodology used was quantitative method. This study was carried out using a questionnaire consisted of 70 items adapted from Gardner’s Attitude/Motivation Test Battery (AMTB) and was distributed to 100 semester 4 students from four departments of PSMZA. The data was analyzed using SPSS. Cohen’s standard was used to evaluate the correlation coefficient, where items with 0.50 or larger were highlighted which represented a strong association. Findings had shown these students’ attitude and motivation towards spoken English had strong correlation with some of the items that helped to boost their motivation in spoken English. These findings indicated the importance of different strategies to be implemented by the English language educators to enhance students’ motivation in communicative English subjects.